(RE)THINKING THE INTERVIEW: A LOOK FROM TRASNCRIPTIONS: UM OLHAR A PARTIR DE TRANSCRIÇÕES - de Souza, Ana Clara Alves; Lessa, Bruno de Souza; Lopes, Fernando Dias (Cadernos de Linguagem e Sociedade, 2018)
This paper aims to discuss the relevance of the researcher’s previous study and preparation to conduct academic interviews. The reflection proposed here originated from the transcription work performed during twelve months in Management as well as related areas. This paper’s contribution lies in the weight given to the effort needed to prepare, choose and perform the interview as a technique of qualitative data collection, insofar as mistakes in such conduction might compromise both the analysis and the results reached in the research.